MICRODISTRIBUTION OF PRIMORDIAL NOBLE GASES IN CM CHONDRITES DETERMINED BY IN SITU LASER MICROPROBE ANALYSIS: DECIPHERMENT OF NEBULAR PROCESSES - NOBLE GASES, CARBON AND AN ESCA STUDY - Nakamura T.; Nagao K.; Takaoka N. (My University, 1999)
In situ noble gas analyses using a laser microprobe with a beam diameter of 50-100 μm were performed on thin slices of Murchison and Yamato (Y-) 791198 CM carbonaceous chondrites in order to see microdistribution of primordial noble gases. Petrographic observations prior to noble-gas analyses showed that the two meteorite slices are entirely composed of chondrules, PCPs (poorly characterized phases) and other chondritic components that are rimmed by layers of fine-grained dust. Based on an existing classification scheme for texture of CM chondrites, the two samples are classified as primary accretionary rocks (PARs). The noble gas analyses showed that primordial noble gases are rich in the fine-grained rims around chondrules in the two meteorite slices. This suggests that large amounts of carrier phases of the primordial noble gases in CM chondrites are located in these rims which seem to have accreted on the surfaces of chondrules prior to the formation of the meteorite parent bodies. Rims on different chondrules within a given meteorite showed similar concentrations of heavy primordial noble gases, suggesting that phase Q is distributed homogeneously in the rims and possibly in the nebular region where the chondrules had acquired their dust rims. (20Ne)diamond/(20Ne)Q ratios are relatively constant among rims in a given meteorite, indicative of homogeneous mixing of interstellar diamonds and phase Q on a 10 μg scale. One location in a rim around a chondrule in the Murchison sample showed an enrichment of 22Ne, which suggests presence of carrier phases of Ne-E in the rim.A stepped heating analysis of a chip of Y-791198 was carried out to characterize the noble gases of bulk PAR. Abundances of primordial noble gases are only ~50% of those of rims around chondrules, consistent with the relative abundances of gas-rich fine-grained material and gas-poor chondrules and inclusions in PAR. Solar gases were not detected, which implies that PARs, the primitive CM bodies, had grown to at least centimeter size in a dense solar nebula which shielded these objects from direct exposure to solar wind.